1989
DOI: 10.1007/bf01540354
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of food protein antigen in infants with food protein-induced enterocolitis

Abstract: Increased gastrointestinal absorption of intact antigen with systemic immunization has been considered a major etiologic factor in the development of food sensitivity. We attempted to test this hypothesis in infants with suspected food protein-induced entercolitis by measuring serum ovalbumin (OVA) concentrations after ingestion of egg white (prior to the performance of good challenges to establish this diagnosis). We first noted significant underestimation of serum OVA concentrations in the presence of even l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This local inflammation may be mediated by activated peripheral mononuclear cells, increased TNF-α, and decreased expression of TGF-β receptors in the intestinal mucosa [23]. However, baseline antigen absorption is normal and does not predispose to FPIES [41]. Methomoglobinemia described in case of severe acute FPIES have been attributed to the local intestinal inflammation [24].…”
Section: Pathophysiology Of Food Protein-induced Enterocolitis Syndromementioning
confidence: 99%
“…This local inflammation may be mediated by activated peripheral mononuclear cells, increased TNF-α, and decreased expression of TGF-β receptors in the intestinal mucosa [23]. However, baseline antigen absorption is normal and does not predispose to FPIES [41]. Methomoglobinemia described in case of severe acute FPIES have been attributed to the local intestinal inflammation [24].…”
Section: Pathophysiology Of Food Protein-induced Enterocolitis Syndromementioning
confidence: 99%
“…Previous endoscopic evaluations and biopsies in infants with FPIES highlight inflammatory responses in the colon, with diffuse colitis and variable ileal involvement. Colon mucosa can be mildly friable or show severe spontaneous hemorrhage, and minute ulcers can be found [3, 11,36]. Crypt abscesses are identified in some patients [37].…”
Section: Pathologymentioning
confidence: 99%
“…Data from a challenge-based study in Korea show that CM-FPIES and soy FPIES may resolve significantly more rapidly than previously assumed [25]. In pooling data from multiple small cohorts, patients seem to be able to tolerate CM at around 3 years of age, although results from 2 recent large cohorts showed that tolerance developed later [13,15,21,24,25,37,38,[45][46][47][48][49][50][51][52][53][54][55][56][57][58]. In a large US case series, the median age of resolution for CM-FPIES was 5.1 years, and in the UK, 25% of the patients had persistent CM-FPIES at 8 years of age [59].…”
Section: Fpies Caused By Cm/soymentioning
confidence: 99%
“…This inflammation is hypothesized to result in increased intestinal permeability leading to a fluid shift into the gastrointestinal lumen. In acute FPIES, the effect of ondansetron on resolution of emesis suggests a potential neuroimmune mechanism and serotonin pathway involvement [57]. Current evidence regarding potential immunologic pathogenic mechanisms is summarized in Table 9.…”
Section: Pathophysiologymentioning
confidence: 99%